Oral Melanocytic nevi : review of literature and report of a case - Cyril Pandarakalam; Varghese V Ipe; P M Shameena; S Sudha (Wolters Kluwer Medknow Publications, 2007)
Melanocytic nevi are uncommon lesions of the oral cavity. Most reports are of isolated cases or of a small series of cases. The purpose of this article is to report a case of oral melanocytic nevi and to review the literature. Review of literature revealed that about one third of patients with malignant melanoma had preexisting macular pigmentation present. Therefore, removal of all lesions suspected to be nevi is recommended. Oral lesions are uncommon and usually small that excision seems advisable.